Математико-статистическая оценка среднеранней группы сортов картофеля на предмет их национального приоритета - СТРОЯНОВСКИЙ В. С. (Stiinta Agricola, 2015)
In Ukraine, potato cultivation has been reduced in the large farms and increased in the private sector represented by small farms. Therefore, the requirements for potato varieties have been changed. The most demanded ones are those that have excellent taste, are resistant to a monoculture, high-yielding and are more biologically suitable to local soil and climatic conditions. The purpose of our research is to identify the productivity of different potato varieties such as: Adrett (German selection), Karin (Czech selection), Space and Caesar (Dutch selection) and Bereginya (Ukrainian selection). The following research methods were used: general scientific – a hypothesis (developing a scheme of the experiment), induction – deduction (comparison and generalization), abstraction – specification (paying attention to the main factors), modeling (schemes and charts), formalization (mathematical presentation of processes and conclusions), abstraction (logical decisions), etc.; special – field experiments (studying the biology and agrotechnics of a crop) and laboratory experiments (biological studies of crops, chemical analyses, etc.). The mathematical and statistical evaluation of research results of the mid-early group of potato varieties in terms of their national priority has proven that the yielding potential of foreign selection varieties is practically at the same level as the Ukrainian ones, correspondingly (27.7 t/ha - 29.4 t/ha, the Bereginya variety). Реферат. В последние годы в Украине сокращаются посадки картофеля в крупнотоварных хозяйствах и увеличиваются в индивидуальном секторе мелких землепользователей фермерского формата. Это изменило требования к сортам. Наиболее востребованными становятся высоковкусовые, устойчивые к монокультуре, высокоурожайные, биологически более соответствующие местным почвенно-климатическим условиям. Цель наших исследований заключалась в выявлении продуктивности разных сортов картофеля (Адрреты – немецкой селекции, Карин – чешской, Космос и Цезарь – голландской селекции, Берегиня – украинской). Методы исследований: общенаучные – гипотеза (разработка схемы опыта), индукция – дедукция (сравнение и обобщение), абстрагирование – конкретизация (обострение внимания на главных факторах), моделирование (схемы, графики), формализация (математическое изложение процессов и выводов), абстракция (логические решения) и др.; специальные – полевой (исследование биологии и агротехники культуры) и лабораторный (биологические исследования растений, химические анализы и т.п). Математико- статистическая оценка результатов исследований среднеранний группы сортов картофеля на предмет их национального приоритета, доказала, что урожайный потенциал сортов иностранной селекции практически одинакового уровня с украинским, соответственно (27,7 т/га, против – 29,4 т/га, (St) сорт Берегиня).